Implementasi Moderasi Beragama Menumbuhkan Sikap Toleransi Umat Hindu Kaharingan di Kabupaten Barito Utara - Edung, Tardi (Dharma Duta, 2024)
This study aims to analyze the implementation of religious moderation in fostering tolerance among Hindu Kaharingan communities in Barito Utara Regency. Religious moderation is considered an essential strategy to strengthen interreligious harmony, particularly in regions characterized by cultural and religious diversity such as Barito Utara. This research employed a qualitative approach with data collected through observation, in-depth interviews, and documentation study. The findings reveal that the values of religious moderation are internalized through religious education, customary activities, and social interactions among religious communities. Huma Betang, as a symbol of Dayak communal life, also serves as an effective medium in fostering understanding and the practice of tolerance. Supporting factors include the roles of traditional leaders, religious leaders, and local government support. However, several challenges remain, such as persistent stereotypes between groups and limited understanding of local wisdom among younger generations. This study concludes that religious moderation significantly contributes to strengthening tolerance among Hindu Kaharingan communities and can serve as a model for maintaining interreligious harmony in multicultural regions.